Electron beam induced modifications in the microstructure of PVA/Li2B4O7 polymer films: Positron annihilation study. (October 2018) - Ismayil,; Ravindrachary, V.; Sanjeev, Ganesh; Praveena, S.D.
Abstract: The films of 5 wt% Lithium Tetra Borate (Li2 B4 O7 ) doped Poly(vinyl alcohol) (PVA) were prepared by solution casting method. The prepared films were irradiated with different doses of 8 MeV electron beam. Fourier Transform Infrared (FTIR) Spectroscopy, UV–Visible Spectroscopy, electrical conductivity measurements and Positron Annihilation Lifetime (PAL) Spectroscopy were used to study the effects of electron radiation on the microstructure and properties of these films. The FTIR results show that the radiation induced chain scission in Li2 B4 O7 doped PVA, which affects the physical properties of the composite film. The variation of optical parameters for instance optical energy band gap, activation energy were obtained from UV–Visible absorption spectra, which reveals the formation of additional energy levels within the band gap due to the creation of defects and carbonaceous clusters upon irradiation. The conductivity of the sample was found to increase as the electron dose increased. It was found from the PAL study that the free volume size of the polymer increases with electron dose, which facilitates the micro-Brownian motions of the segmental polymer chain backbone. Consequently the motion of Li + ions within the polymer segment will be speeded up. Accordingly ion transport within the polymer matrix strongly depends on rearrangement of free volume adequate to allow ion transport. Highlights: Microstructural modifications in electron irradiated Li2 B4 O7 /PVA are reported. Formation of defects takes place due to chain scission process upon irradiation. The polymeric free volume size V f increases with the increase of electron dose. Higher V f facilitates the micro-Brownian motion of the polymer segment. The ionic transport depends on the probability redistribution of the free volume.